Effect of productive discussion on written argumentation in earth science classrooms. Issue 1 (10th February 2020) - Short, Rachel A.; Van der Eb, Marina Y.; McKay, Susan R.
Abstract: Active teachers noted persistent problems in their classrooms, including low levels of student engagement and gaps in students' use of evidence in forming arguments. Earth Science students provided written responses to two questions using the previously implemented Claim, Evidence, Reasoning (CER) framework. The first question was answered without a preceding discussion whereas the second question was answered following a discussion protocol—no discussion, discussion without Talk Science, and discussion with Talk Science. A ninth grade teacher more comprehensively implemented Talk Science by incorporating statements from all four goals whereas a seventh grade teacher did not. As a result, ninth grade students improved their use of evidence, reasoning, and content, but seventh graders did not show the same improvements. All students valued the discussion, but this study shows that Talk Science discussions can be used to improve students' content knowledge and CER argumentation skills.